Cloud cover feedback moderates Fennoscandian summer temperature changes over the past 1000 years - Young, Giles H.F.; Gagen, Mary H.; Loader, Neil J.; McCarroll, Danny; Grudd, Håkan; Jalkanen, Risto; Kirchhefer, Andreas; Robertson, Iain
2019